New polynomial exponential distribution: Properties and applications - Abdelfateh Beghriche; Halim Zeghdoudi; Vinoth Raman; Sarra Chouia (Statistics in Transition new series (SiTns), 2022)
The study describes the general concept of the XLindley distribution. Forms of density and hazard rate functions are investigated. Moreover, precise formulations for several numerical properties of distributions are derived. Extreme order statistics are established using stochastic ordering, the moment method, the maximum likelihood estimation, entropies and the limiting distribution. We demonstrate the new family's adaptability by applying it to a variety of real-world datasets.
Keywords: 519; exponential distribution; Xgamma distribution; Lindley distribution; quantile function stochastic ordering; maximum-likelihood estimation; XLindley distribution